The Role of Sales Consultants in the Direct Marketing Strategy of Honda Kebon Jeruk West Jakarta in the Covid-19 Pandemic Era - Sugeng Dwi Nugroho; Denik Iswardani Witarti (GoAcademica Research & Publishing, 2021)
Business actors have their way of finding and getting new customers. They develop the right marketing strategy to get new customers because they will win the business competition with their competitors. This study uses a qualitative research method with a case study approach the data used in primary data and secondary data. The methods used in data collection are interviews, observation and document review. Sampling using purposive sampling. The data analysis methods used are data reduction, data display, and conclusions drawing/verification methods. From the research results, it can be seen that: 1) Honda Kebon Jeruk has a breakthrough, namely collaborating with E-commerce such as Tokopedia in marketing their products; 2) Direct Marketing used in Honda Kebon Jeruk includes social media marketing, direct mail, telemarketing, digital marketing, and direct marketing; and 3) The role of sales consultants is significant in the success of the marketing strategy made by Honda Kebon Jeruk using the face to face customer method.